PENGARUH KONSENTRASI NAA DAN KINETIN TERHADAP PERTUMBUHAN TANAMAN KRISAN SECARA IN-VITRO - Ida Royani; Any Fatmawati (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2016)
ABSTRACT: In general, this study aims to determine the effect of concentration of NAA and Kinetin the number of shoots and roots in chrysanthemum plants in vitro. The explants were used chrysanthemum sterile. The background of this research is the growing demand for chrysanthemums from year to year as an ornamental and medicinal materials. The research is a scheme would experiment with completely randomized (CRD) with three replications. The medium used was MS medium with added plant growth regulators NAA at a concentration of (0-3) mg / L and the concentration of Kinetin (0-3) mg / L. The parameters in this study is the number of shoots and roots. Data were analyzed using ANOVA two-lane data obtained when normal and homogeneous, when the F test results were significantly different (significantly) conducted a further test by test Honestly Significant Difference (HSD) at the 5% significance level. Using the Kruskal-Wallis test if the data obtained is not normal and is not homogeneous, when the F test results were significantly different (significantly) conducted a further test with Mann-Whitney test at a significance level of 5% and using descriptive if the data obtained are not eligible to be tested parametric and non-parametric. Outcomes of this study are: (1) article published in the journal ISSN.